Altmetrics in Practice: Librarian and LIS Faculty Views - Miles, Rachel A.; Sutton, Sarah; Konkiel, Stacy (My University, 2016)
Altmetrics measure the impact of scholarship via mentions in social media and other non-traditional venues. For librarians and faculty, altmetrics are also a new area for research. The focus of this presentation is the results of surveys of academic librarians’ and LIS scholars’ awareness and use of altmetrics.
Sutton, Sarah, Konkiel, Stacy, and Miles, Rachel. "Altmetrics in Practice: Librarian and LIS Faculty Views," Electronic Resources & Libraries Conference. (Austin, TX). 4 April 2016. Presentation.
Keywords: altmetrics; bibliometrics; academic libraries; scholarly communication; research impact; research assessment